Molecular docking, prediction of drug-likeness properties, and toxicity risk assessment of compounds from Cinnamomum zeylanicum as inhibitors of Dengue DEN2 NS2B/NS3. - Frimayanti, Neni; Fernando, Armon; Rahmah, Rizka I’zaa; Iskandar, Benni (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Dengue hemorrhagic fever (DHF) is a serious mosquito-borne disease caused by the dengue virus, most often transmitted by the bite of female Aedes aegypti mosquitoes. In Indonesia, the number of DHF cases has steadily increased since the disease was first reported, underscoring the urgent need for effective treatments. This study used in silico methods to explore the potential of three bioactive compounds from Cinnamomum zeylanicum i.e. cinnamaldehyde, α-terpineol, and chavicol as inhibitors of the dengue virus NS2B/NS3 protease and evaluated their drug-likeness and potential toxicity. The compounds sourced from the NADI database were compared with panduratin A as a positive control. Molecular docking was performed using the Molecular Operating Environment (MOE) 2023.0901 software, and drug-likeness and toxicity predictions were performed using SwissADME and Protox-II. Among the tested compounds, α-terpineol exhibited the strongest potential to inhibit NS2B/NS3, while all three met the standard drug-likeness criteria. Notably, α-terpineol demonstrated the most favorable safety profile compared to cinnamaldehyde, chavicol, and panduratin A.